Physical and mechanical studies of kaolin-based geopolymer masonry brick - Muhammad Faheem Mohd Tahir (School of Materials Engineering, 2015)
This study focuses on the production and properties of geopolymer brick made with kaolin as its geopolymer raw material. The geopolymer raw material that was used in this study which is kaolin was locally supplied by Kaolin Industries Sdn. Bhd. The kaolin based geopolymer brick was produced by mixing sand, kaolin and alkaline solution consist of sodium silicate and sodium hydroxide with various ratiosby using geopolymer brick making machine. Then the geopolymer samples had been tested in the laboratory to determine its compressive strength, density and water absorption properties in order to identify the optimum ratios of all the parameters. The whole testing was done accordance to the standard.